Gravity Versus Tectonics: The Case of 2016 Amatrice and Norcia (Central Italy) Earthquakes Surface Coseismic Fractures. Issue 4 (11th April 2019) - Di Naccio, D.; Kastelic, V.; Carafa, M. M. C.; Esposito, C.; Milillo, P.; Di Lorenzo, C.
Abstract: The 2016 central Apennines earthquake sequence was caused by slip on an extensional fault system and resulted in sizable coseismic surface deformation. The most evident effects occurred along the western slope of Mount Vettore, a geologically and morphologically complex mountain ridge. Steep topography and rheological contrasts are known to have strongly controlled the coseismic deformation pattern during a number of different earthquakes that occurred in mountainous areas worldwide. Nevertheless, so far the role of seismically induced slope failures has not been taken into account in the interpretation of the surface fractures caused by the 2016 earthquake sequence. We modeled the static and dynamic slope stability along the western flank of Mount Vettore and in the underlying Piano Grande plain. Combining the slope stability analysis with geomorphic and geological analyses, we show that the coseismic fractures are distributed along the most unstable areas of the western flank of Mount Vettore and can be partly explained by shaking‐induced mechanisms such as gravity‐driven displacement, compaction, and secondary ground failure. Conversely, in the Piano Grande plain the fracture pattern is not affected by topography or rheology contrasts, suggesting that it is positively caused by tectonic faulting. Different processes, such as gravitational and erosional‐depositional phenomena, may contribute to the exposure of fault scarps during both the coseismic and interseismic periods. Attributing the surface deformation entirely to tectonic faulting, especially in complex mountainous terrains such as the Apennines, may lead to an incorrect assessment of fault displacement and fault slip rate and hence of seismic hazard. Key Points: We assess the topographic and rheological influences on coseismic surface deformation along Mount Vettore after the 2016 earthquake sequence The largest coseismic offsets occurred in the most unstable zones of Mount Vettore, indicating potentially significant nontectonic deformation The coseismic fractures in the Piano Grande were not affected by topography or rheology contrasts, supporting a tectonic origin